Pendampingan dalam Meningkatkan Kualitas Produk dan Pelayanan dalam Memenuhi Kepuasan Pelanggan - Army Cahya Putra Rustamaji; Sinta Sundari Heriyanti; Suhendra Suhendra; Arif Widodo Nugroho (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
In the era of globalization and intense business competition, the quality of products and services is crucial for competitiveness, particularly for Micro, Small, and Medium Enterprises (MSMEs) like Angkringan, a traditional culinary business in Indonesia. The article explores Total Quality Management (TQM) as a strategy for these businesses to enhance operational efficiency, reduce waste, and improve customer satisfaction. The study involved direct interviews with the owner of Angkringan D’Amerta to analyze TQM application covering quality control procedures, customer satisfaction, and continuous improvement. Results indicated a deeper understanding of customer preferences and the importance of maintaining quality standards through the training of staff and development of operational procedures. The findings suggest that effective quality management can significantly enhance business performance and customer engagement in the digital era. The paper advocates for routine training, implementation of standard operating procedures, and regular quality assessments to ensure consistent service and product quality.